Differentiation of Human Limbal‐Derived Induced Pluripotent Stem Cells Into Limbal‐Like Epithelium. (28th July 2014) - Sareen, Dhruv; Saghizadeh, Mehrnoosh; Ornelas, Loren; Winkler, Michael A.; Narwani, Kavita; Sahabian, Anais; Funari, Vincent A.; Tang, Jie; Spurka, Lindsay; Punj, Vasu; Maguen, Ezra; Rabinowitz, Yaron S.; et al.
Abstract : The purpose was to generate human induced pluripotent stem cells (iPSCs) and direct them to limbal differentiation by maintaining them on natural substrata mimicking the native limbal epithelial stem cell (LESC) niche (feederless denuded human amniotic membrane [HAM] and denuded corneas). Limbal‐derived iPSCs had fewer unique methylation changes than fibroblast‐derived iPSCs, suggesting retention of epigenetic memory during reprogramming, which may facilitate redifferentiation back to limbal cells. Limbal iPSCs cultured for 2 weeks on HAM developed markedly higher expression of putative LESC markers than did fibroblast iPSCs. Abstract : Limbal epithelial stem cell (LESC) deficiency (LSCD) leads to corneal abnormalities resulting in compromised vision and blindness. LSCD can be potentially treated by transplantation of appropriate cells, which should be easily expandable and bankable. Induced pluripotent stem cells (iPSCs) are a promising source of transplantable LESCs. The purpose of this study was to generate human iPSCs and direct them to limbal differentiation by maintaining them on natural substrata mimicking the native LESC niche, including feederless denuded human amniotic membrane (HAM) and de‐epithelialized corneas. These iPSCs were generated with nonintegrating vectors from human primary limbal epithelial cells. This choice of parent cells was supposed to enhance limbal cell differentiation from iPSCs by partial retention of parental epigenetic signatures in iPSCs. When the gene methylation patterns were compared in iPSCs to parental LESCs using Illumina global methylation arrays, limbal‐derived iPSCs had fewer unique methylation changes than fibroblast‐derived iPSCs, suggesting retention of epigenetic memory during reprogramming. Limbal iPSCs cultured for 2 weeks on HAM developed markedly higher expression of putative LESC markers ABCG2, ΔNp63α, keratins 14, 15, and 17, N‐cadherin, and TrkA than did fibroblast iPSCs. On HAM culture, the methylation profiles of select limbal iPSC genes (including NTRK1, coding for TrkA protein) became closer to the parental cells, but fibroblast iPSCs remained closer to parental fibroblasts. On denuded air‐lifted corneas, limbal iPSCs even upregulated differentiated corneal keratins 3 and 12. These data emphasize the importance of the natural niche and limbal tissue of origin in generating iPSCs as a LESC source with translational potential for LSCD treatment.